On an Alternative Approach to Pricing General Barrier Options - Michael Suchanecki (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
In this paper, an alternative approach to pricing barrier options is presented that relies on the use of the first hitting time density to the barrier. The lateral Chapman-Kolmogorov relation is used as a major tool in order to determine option prices. It turns out that this approach allows for pricing barrier options with more general payoffs and with general continuous Markovian stochastic processes as underlying (at least numerically). As an illustrative example, a simple down-and-in call option is considered and its well-known closed form pricing formula is obtained.
Keywords: G13; 330; Barrier options; first passage time density; first hitting time density; lateral Chapman-Kolmogorov relation